Continuous flow as an enabling technology: a fast and versatile entry to functionalized glyoxal derivatives. Issue 11 (1st March 2021) - Lima, Fabio; Meisenbach, Mark; Schenkel, Berthold; Sedelmeier, Joerg
Abstract : Continuous Flow methods to access glyoxal derivatives, which serve as valuable precursors for heterocyclic chemistry. Abstract : We herein report two complementary strategies employing organolithium chemistry for the synthesis of glyoxal derivatives. Micro-mixer technology allows for the generation of unstable organometallic intermediates and their instantaneous in-line quenching with esters as electrophiles. Selective mono-addition was observed via putative stabilized tetrahedral intermediates. Advantages offered by flow chemistry technologies facilitate direct and efficient access to masked 1, 2-dicarbonyl compounds while mitigating undesired by-product formation. These two approaches enable the production of advanced and valuable synthetic building blocks for heterocyclic chemistry with throughputs of grams per minute.